Innovation for sustainable development: a designerly perspective (African Journal of Science, Technology and Social Sciences, 2022)
There is growing consensus that the 21st Century is the African Century, However, this noble vision cannot happen by default - it must catalysed by Design Thinking - by a deliberate and strategic drive to achieve sustainable development for the continent's denizens. This presentation showcases a number of innovative solutions emerging from the creative minds of Africans with solutions for Afrika*. The exemplars discussed herein advocate an ethical and socially conscious ethos that embraces transdisciplinary as a means of co-creation and co-production. Further, the presentation makes a strong case for disciplinary imagineering beyond the traditional STEM approach, to one of STEAM - a more inclusive and empathic design approach that takes cognisance of the design, the arts and humanities.  For Afrika to achieve its lofty ambitions and play an active role in the 4th and 5th Industrial Revolutions, we must adopt a more holistic Quadruple Helix model of partnership (that includes Academia; Business/Industry; Community/Civil Society; and Government). In conclusion, this presentation exhorts innovators and inventors in academic institutions to contribute to Afrika's sustainable development through projects that make a marked social impact in the real world...